2016
DOI: 10.1017/s1368980016000082
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of portion size estimation aids: precision, ease of use and likelihood of future use

Abstract: Objective: The present study aimed to evaluate the precision, ease of use and likelihood of future use of portion size estimation aids (PSEA). Design: A range of PSEA were used to estimate the serving sizes of a range of commonly eaten foods and rated for ease of use and likelihood of future usage. Setting: For each food, participants selected their preferred PSEA from a range of options including: quantities and measures; reference objects; measuring; and indicators on food packets. These PSEA were used to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…The lack of a consistent pattern with regard to the impact of food texture on PSEE performance also confirms previous findings, 15 , 17 , 51 suggesting that estimation accuracy may interact with other uncontrolled factors such as a participant’s experience, level of attention, willingness to cooperate, or education 17 , 51 . A study in British adults in which photos were compared with weighed foods reported less accuracy in estimating French fries, mashed potatoes, and spaghetti than in estimating cornflakes, 92 while a study in Norwegian children 93 found that mashed potatoes and cornflakes, in addition to other shaped or amorphous foods, were the most accurately estimated foods.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The lack of a consistent pattern with regard to the impact of food texture on PSEE performance also confirms previous findings, 15 , 17 , 51 suggesting that estimation accuracy may interact with other uncontrolled factors such as a participant’s experience, level of attention, willingness to cooperate, or education 17 , 51 . A study in British adults in which photos were compared with weighed foods reported less accuracy in estimating French fries, mashed potatoes, and spaghetti than in estimating cornflakes, 92 while a study in Norwegian children 93 found that mashed potatoes and cornflakes, in addition to other shaped or amorphous foods, were the most accurately estimated foods.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, a wider range of food types needs to be explored with such tools, as performance depended heavily on food texture, and no consistent pattern was seen across studies (ie, some studies favored food picture–based PSEEs for foods with defined shape 18 , 56 and food models for amorphous food, 11 while others showed the opposite 56 ). Household utensils, on the other hand, were the least precise and least accurate in at least 2 studies, 51 , 56 as observed in some Group 1 studies 5 , 32 . While simple instruments may be nonintrusive, quick to complete, and suitable for low-literacy groups or those not speaking the language of the host country, limitations in the validity and reproducibility of such tools need to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research related to such tools has focused on whether they improve the accuracy of portion size estimation 18,48 . One study, however, assessed the usage of portion-control tools and found that household measures were rated as the easiest to use and reported to be the most likely to be used again 19 . The current trial found that household measures were initially the most frequently used tool of the four provided, but after three months their reported use decreased substantially.…”
Section: Discussionmentioning
confidence: 99%
“…When restricting energy intake, individuals can eat their usual amount of food by consuming larger portions of low-energy-dense foods (vegetables, fruits, lean proteins) while limiting portions of higher-energy-dense foods (high-fat, low-water foods). The use of tools such as food scales and household measures could improve the implementation of such recommendations 18,19 . Surprisingly few studies have examined whether use of portion-control tools is sustained over time and whether they facilitate weight management; however, promising results have been found using plates that indicate appropriate proportions of meal components 2022 .…”
Section: Introductionmentioning
confidence: 99%